Simulação do efeito residual da atrazine em cenoura - Furlan, Renan G. [UNESP]; Martins, Juliano F. [UNESP]; Santos, Juciléia I. [UNESP]; Alves, Pedro Lca. [UNESP] (FapUNIFESP (SciELO), 2016)
Atrazine is an herbicide recommended for the corn crop,but little information is available on its residual effect on vegetables that could be grown in succession. The objective of this research was to evaluate the residual simulation of atrazine doses in the substrate on the development and production of ‘Brasília’ carrot. Treatments consisted of eight decreasing doses of atrazine (250,25.0,2.5,0.25,0.025,0.0025,0.00025 and 0 g a.i./ha) starting on 1/10 of the concentration dose commercially recommended for sweet corn (2500 g a.i./ha). Experimental design was completely randomized with four replications. Experimental units consisted of plastic pots with a capacity of 20 L. The carrot plants were evaluated for percentage and emergence speed index (at 7,14 and 21 days after application),mortality,length and perimeter of roots,root fresh weight and dry weight of aboveground part at 29 and 90 days after application (DAA). We concluded that residual up to 250 g a.i./ha atrazine might cause initial biomass reduction in carrot (29 DAA),without,however,damaging its production of roots.
Residual effect of atrazine in carrot crop
Keywords: Carry-over; Daucus carota; Herbicide